(untitled) (Green University Review of Social Sciences, 2022)
Sustainability and sustainable development are now centre-stage in economic, environmental, social and educational activities around the world. However, these are not only complex concepts, but the perspective and understanding vary in different places, time, geographical and economic conditions. What is of particular relevance to Bangladesh, is the importance of educating for sustainability while emphasising values education and responses to the current realities that have resulted from factors, such as economic development and climate change. This is particularly the case in primary education which builds the foundation for preparing children for dealing with future challenges. This paper argues that sustainability attitudes can be communicated by embedding folk values in primary education as a way to communicating complex concepts and supporting the sustainable development journey of Bangladesh which as a country has to respond to issues related to population growth, poverty, inequality and climate change. It investigates the place of values and wisdom from the country’s rich folklore as a tool in formal and non-formal primary education in Bangladesh to encourage a holistic approach to sustainability which looks at the needs of people within the boundaries of the natural environment. Green University Review of Social Sciences Dec 2021; 7(1-2): 1-21